Multimedia Augmented Reality Technology in Daily Basic Knowledge Learning Media for Early Childhood and Kindergarten - Ady Purna Kurniawan; Niswa Nafiah Sartono; Fahmi Alhamda Zikra; Aulia Izzatul Ulwan (IJAIT (International Journal of Applied Information Technology), 2019)
Education for children from an early age is essential because it can affect the growth of children's knowledge at a later age. The introduction of basic daily things can be given to children to make them feel enjoy learning fun objects and make them critical. Educational institutions have widely used the use of information technology from the initial level such as kindergarten. Therefore, the development of learning media is for supporting parents and teachers in providing basic daily knowledge for children. Augmented Reality has features with combining 3D object animation and audio so that the teaching material displayed can be seen in real. This learning media has a very simple and easy to use the display with some menu. When each menu is selected, it will go directly to the camera mode for scanning the teaching marker. This learning media can be used both at school and at home, as well as by teachers or parents and even the child itself.